Global burden of esophageal cancer attributable to smoking: a systematic analysis for the Global Burden of Disease Study 2019 - Wu, Shilong; Jiang, Wenfa; Li, Jiufei; Wu, Zeqin; Xu, Chenyang; Xie, Ning (Frontiers in Oncology, 2023)
Background: Epidemiological trends of esophageal cancer attributable to smoking remain unclear. This study aimed to estimate the spatiotemporal trends of esophageal cancer burden attributable to smoking to assist in global esophageal cancer prevention and smoking cessation.: Data on esophageal cancer attributable to smoking were obtained from the Global Burden of Disease Study 2019. The number and age-standardized rates on esophageal cancer mortality (ASMR) and disability-adjusted life years (ASDR) were analyzed by age, sex, and location. Joinpoint regression analysis was used to analyze the temporal trends of esophageal cancer burden attributable to smoking over 30 years. Results: In 2019, the number of global esophageal cancer deaths and disabilityadjusted life-years (DALYs) attributable to smoking was approximately 203 thousand and 475 million respectively. The global esophageal cancer deaths and DALYs due to smoking were about 1.5-fold increased from 1990 to 2019, but the corresponding ASMR and ASDR had decreased. The heaviest burden occurred in East Asia, Mongolia, and the middle socio-demographic index (SDI) region. The male to female ratio was about 12.7 in the esophageal cancer deaths and DALYs and was about 14.3 in the ASMR and ASDR. The heaviest burden appeared in 60-74 years age group. The estimated annual percentage change (EAPC) in ASMR was highly negatively associated with ASMR in 1990 (ρ = -0.41, p < 0.001) and SDI in 2019 (ρ = -0.29, p < 0.001).Despite reductions in ASMR and ASDR, the esophageal cancer burden attributable to smoking remains heavy, especially in middle SDI regions. Active tobacco control can reduce esophageal cancer burden.